Finance and Development, March 2013. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
Two years ago, citizens in the Arab world-fired by their ideals and visions of a better life-ignited a social movement that inspired people around the globe. In Egypt, Jordan, Libya, Morocco, Tunisia, and Yemen-the so-called Arab countries in transition-people embraced change, ushering in a new era. This issue of F and D looks at the difficulties of this transition, focusing on long-standing forces that shape the region's economy and offering options for moving ahead to achieve strong, inclusive growth. -- Masood Ahmed, Director of the IMF's Middle East and Central Asia Department, maps out an agenda for modernizing and diversifying the region's economies in 'Toward Prosperity for All.' -- In 'Freedom and Bread Go Together,' Marwan Muasher addresses the intersection of economic progress and political change. -- Vali Nasr, in a Point of View column, underscores the vital role small and medium-sized enterprises play in a successful democratic transition. Elsewhere in this issue, we look at how surging oil and gas production in the United States could shake up global energy markets; the effect of uncertainty on economic growth; and Mexico's competitiveness rebound. F and D's People in Economics series profiles Christina Romer, former chair of the U.S. Council of Economic Advisers and an architect of the U.S. stimulus package; and the latest installment in our Back to Basics series explains how structural policies help to both stabilize and strengthen economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet